Plastic deformation and rheology of the sinistral strike‐slip ductile shear zone in the Bayan Nuru area, Alxa Zuoqi, NW China: Product of subduction of Paleo‐Pacific Plate. (2nd December 2019) - Feng, Yipeng; Zhang, Weijie; Wang, Genhou; Li, Dian; Lu, Yang
Abstract : The Bayan Nuru ductile shear zone is located in the Yabulai–Bayan Nuru tectonic belt of the middle part of the southern Central Asian Orogenic Belt (CAOB) and east of the Langshan tectonic belt. This article is the first report on the Bayan Nuru ductile shear zone, and provides dynamic, kinematic, and geochronological data of the shear zone. Accurately determining the shear orientation and estimating the shearing age of the Bayan Nuruductile shear zone, has important reference value and significance for understanding the tectonic evolution in Alxa during "Yanshan movement" period. All shearing signatures, including asymmetrical folds, rotated porphyroclasts, "domino" structures, "mica fishes, " S–C fabrics, and asymmetric stress shadows, developed in the shear zone, indicate sinistral shear. The temperature environment at the time of formation of the shear zone was determined by the mineral deformation thermometer and EBSD quartz C‐axis fabric analysis. The temperature was 350–550°C. The differential stress (σ) was estimated to be 44.31–97.94 MPa and the strain rate(έ) to be 10 −14 s −1 (350°C) and 10 −10 s −1 (550 °C). The average kinematic vorticity of the Bayan Nuru NNE‐trending ductile shear zone is 0.93, indicating that the shear zone was dominated by simple shear. The thickness of the ductile shear zone was reduced by 7%–22%. Combined with the age of granitic mylonite (289.53 ± 0.74 Ma) and the NNE‐trending spread feature, the Bayan Nuru ductile shear zone in the western part of the Langshan fault zone may have been formed in the context of continuous compressional intraplate deformation, caused by the subduction of the Paleo‐Pacific Plate at 170–150 Ma.